1993
DOI: 10.1111/j.1365-2249.1993.tb06492.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms resulting in pathogenic anti-mouse erythrocyte antibodies in New Zealand black mice

Abstract: SUMMARYThe New Zealand black (NZB) mouse strain is genetically predisposed to develop, at approximately 6 months of age, a spontaneous and severe autoimmune anaemia caused by production of pathogenic anti-mouse erythrocyte autoantibodies. In order to investigate the molecular mechanisms which lead to anti-mouse erythrocyte autoantibody production we have generated eight anti-mouse erythrocyte MoAbs producing hybridomas from splenocytes of 9-and 12-month-old NZB with spontaneous autoimmune anaemia. IgG2a was th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 35 publications
(38 reference statements)
0
7
0
Order By: Relevance
“…Early studies by Linder and Edgington [61] demonstrated that the target of the NZB MRBC-specific autoantibodies was a glycoprotein of high molecular weight that they referred to antigen 'X'. As indicated above, panels of NZB-derived monoclonal anti-MRBC hybridomas demonstrated heterogeneous V region gene usage [29][30][31], suggesting diversity also in target binding. Autoantibodies extracted from Coombs' positive erythrocytes from actively autoimmune NZB mice, like many (but not all) of the MRBC-specific pathogenic IgG mAbs produced from these mice, immunoprecipitate exclusively Band 3 from MRBC membranes [62][63][64].…”
Section: Specificity Of the Anti-mrbc Response(s)mentioning
confidence: 99%
See 2 more Smart Citations
“…Early studies by Linder and Edgington [61] demonstrated that the target of the NZB MRBC-specific autoantibodies was a glycoprotein of high molecular weight that they referred to antigen 'X'. As indicated above, panels of NZB-derived monoclonal anti-MRBC hybridomas demonstrated heterogeneous V region gene usage [29][30][31], suggesting diversity also in target binding. Autoantibodies extracted from Coombs' positive erythrocytes from actively autoimmune NZB mice, like many (but not all) of the MRBC-specific pathogenic IgG mAbs produced from these mice, immunoprecipitate exclusively Band 3 from MRBC membranes [62][63][64].…”
Section: Specificity Of the Anti-mrbc Response(s)mentioning
confidence: 99%
“…Analyses of VH and VL regions of NZB-derived pathogenic MRBC-specific hybridomas in three different laboratories have demonstrated that the genes encoding these monoclonal autoantibodies exhibit no obvious restriction of the V gene families utilized. Extensive somatic mutation seen within the V region genes [29][30][31] is indicative of an antigen-driven response. Furthermore, these MRBC-specific mAbs use the same general genetic repertoire used in responses to exogenous antigens, supporting the conclusion that the anti-MRBC, as well as exogenous antigen responses, are antigen driven and not due to natural antibodies [29][30][31].…”
Section: Introduction/mouse Models Of Autoimmune Hemolytic Anemiamentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the New Zealand black mouse strain is predisposed to develop AIHA at approximately 6 months of age, which is caused by the production of anti-RBC autoantibodies [45]. The antigen specificities of multiple monoclonal antibodies derived from these mice have been determined [46], and, when injected into other strains of mice, these purified monoclonal antibodies induce autoimmune hemolysis [39].…”
Section: Murine Aiha Modelsmentioning
confidence: 99%
“…These IgM autoantibodies induced in vivo thrombocytopenia through uptake of opsonized platelets (10). In contrast, IgM anti-erythrocyte autoantibodies generated from NZB mice (11) cause anemia through spleen accumulation of agglutinated erythrocytes rather than through erythrophagocytosis (12,13).…”
mentioning
confidence: 99%